Ethno-Nationalism and Electoral Clientelism : The Dayaks' Experience - Neilson Ilan, Mersat (Universiti Malaysia sarawak, 2013)
Discussing the rise of Dayak ethno-nationalism and relate it to the role of patronage politics in Sarawak.